2013
DOI: 10.1080/19425120.2013.786002
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Distribution of Sharks in Northeast Florida Waters and Identification of Potential Nursery Habitat

Abstract: Sharks are considered top predators in many marine ecosystems and can play an important role in structuring community ecology. As a result, it is necessary to understand the factors that influence their abundance and distribution. This is particularly important as fishery managers develop management plans for sharks that identify areas that serve as essential fish habitat, especially nursery habitat. However, our understanding of shark habitat use in northeast Florida waters is limited. The goal of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…Salinity and temperature have important physiological implications for sharks [ 20 , 68 ] and there are numerous examples of their influence on shark habitat use [ 3 , 14 , 36 ]. For example, the occurrence of immature scalloped hammerhead sharks in the north-eastern Gulf of Mexico increased with both salinity and temperature [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity and temperature have important physiological implications for sharks [ 20 , 68 ] and there are numerous examples of their influence on shark habitat use [ 3 , 14 , 36 ]. For example, the occurrence of immature scalloped hammerhead sharks in the north-eastern Gulf of Mexico increased with both salinity and temperature [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of abiotic variables are thought to influence the habitat use of coastal sharks (reviewed in [ 11 ]). For example, water temperature [ 14 ], depth [ 15 ], salinity [ 3 , 16 ], turbidity [ 17 ] and dissolved oxygen concentration (DO; [ 18 , 19 ]) have been identified as important factors for multiple species. Influences of abiotic variables may be dictated by a species’ physiological requirements [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on shark assemblages in the northeast Florida and southeast Georgia coast, a location commonly referred to as the “First Coast” as it was the first area of Florida colonized by Europeans, have demonstrated that this region provides an important habitat for a sizeable number of commercially and recreationally important shark species (McCallister et al ., ; Morgan ). Initial work examining shark abundance in First Coast estuaries demonstrated that at least 11 shark species use inshore waters in this region on a seasonal (late spring to fall) basis, with at least two species, the Atlantic Sharpnose shark ( Rhizoprionodon terraenovae , J. Richardson, 1836) and Blacktip shark ( Carcharhinus limbatus , J. P. Müller & Henle, 1839), making use of the site as juvenile refuge or “nursery” habitat (McCallister et al ., ). More recently, a follow‐up study expanded the total number of shark species that frequent First Coast waters to a minimum of 14 and also reported differences in species and life‐stage composition of catch from inshore estuarine waters and adjacent beach habitats, demonstrating the greater abundance of older ( i.e ., juvenile to mature) life stages in nearshore waters (Morgan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on shark assemblages in the northeast Florida and southeast Georgia coast, a location commonly referred to as the "First Coast" as it was the first area of Florida colonized by Europeans, have demonstrated that this region provides an important habitat for a sizeable number of commercially and recreationally important shark species (McCallister et al, 2013;Morgan 2018). Initial work examining shark abundance in First Coast estuaries demonstrated that at least 11 shark species use inshore waters in this region on a seasonal (late spring to fall) basis, with at least two species, the Atlantic Sharpnose shark (Rhizoprionodon terraenovae, J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation